Distributional Patterns of Polychaetes Across the West Antarctic Based on DNA Barcoding and Particle Tracking Analyses - Brasier, Madeleine J.; Harle, James; Wiklund, Helena; Jeffreys, Rachel M.; Linse, Katrin; Ruhl, Henry A.; Glover, Adrian G. (Frontiers in Marine Science, 2017)
Recent genetic investigations have uncovered a high proportion of cryptic species within Antarctic polychaetes. It is likely that these evolved in isolation during periods of glaciation, and it is possible that cryptic populations would have remained geographically restricted from one another occupying different regions of Antarctica. By analysing the distributions of nine morphospecies, (six of which contained potential cryptic species), we find evidence for widespread distributions within the Western Antarctic region. Around 60% of the cryptic species exhibited sympatric distributions, and at least one cryptic clade was found to be widespread. Additional DNA barcodes from GenBank and morphological records extended the observed range of three species studied here, and indicate potential circum-Antarctic traits. Particle tracking analyses was used to model theoretical dispersal ranges of pelagic larvae. Data from these models suggest that the observed species distributions inferred from genetic similarity could have been established and maintained through the regional oceanographic currents. West Antarctic continental shelf populations may be connected via the Antarctic Circumpolar Current or its coastal Counter Current, dependent on particle release location. Improved understanding of the distribution of Antarctic fauna is essential for predicting the impacts of environmental change and determining management strategies for the region.